"A Difficult Balancing Act": What Planning Involves. (20th October 2022) - Grant, Jill L.
Abstract: Drawing on verbatim transcriptions of over 200 interviews, the article systematically analyzes the use of the concept of "balance" in what planners and others say about the nature and role of planning and planners. Planning involves managing competing aims and economic interests in processes that are simultaneously political and technical: what many call "a balancing act." Discourse analysis of the content and form of utterances involving the root balanc* suggests that the words people choose in describing planning can simultaneously reflect and obscure power relations and decision processes.